PERIOPERATIVE IMMUNOSUPPRESSION IN CANCER PATIENTS: Impact of Anesthetic Techniques - Khamdamov, B.Z.; Ibragimov, N.K.; Rakhimov, B.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Surgical stress and anesthesia are well-documented triggers of transient immunosuppression in cancer patients, potentially promoting tumor progression and metastasis during the perioperative period. Different anesthetic techniques—such as general anesthesia with volatile agents, total intravenous anesthesia (TIVA), regional blocks, and opioid-based analgesia—exert variable effects on immune function. This review summarizes current evidence on how anesthetic modalities influence cellular and humoral immunity in oncologic surgery. Key mechanisms discussed include effects on natural killer (NK) cell activity, cytokine release, neutrophil function, and regulatory T cell populations. The review also examines how these immunological changes may affect oncologic outcomes, including recurrence and survival. Understanding these effects is critical to tailoring anesthesia protocols that minimize immunosuppression and support host defense during the perioperative window. Keywords: Cancer, perioperative immunosuppression, anesthesia, TIVA, immune function, surgical oncology